Ecological Concept of Wayang Stories and the Relation with Natural Conservation in Javanese Society - Sulaksono, D; Saddhono, K (KnE Social Sciences, 2018)
Wayang is one of the Javanese performing arts that has a great value in Javanese society. The aim of this research is to describe and explain the ecological concept of the wayang story in Central Java and the Special Region of Yogyakarta. This qualitative descriptive research uses an ethnographic approach. Data were collected by using domain analysis techniques, taxonomic analysis, compositional analysis, and theme analysis. Data validation uses the extra participation technique, perseverance observation, triangulation, detailed discussion, and auditing. The research found that the ecological concept in wayang stories can be found in some used term and the motto, which relates to the term ‘environment conservation’. This term is found in the narration of the story and the dialog of wayang characters, and some mottos are also found that are related to the nature conservation effort. With regard to the results of this research, it can be said that the ecological concept in wayang stories also has functions relating to natural conservation and preservation for the society in Central Java and the Special Region of Yogyakarta. Keywords: ecological concept, Javanese literature, natural conservation, wayang story